Risk of acute kidney injury following contrast-enhanced CT or MRI in a cohort of 3061 hospitalized children in China - Chen Wang; Chao Zhang; Jihang Sun; Ruohua Yan; Xiaohang Liu; Lulu Jia; Xiaoxia Peng (BMC, 2024)
Abstract Objectives To compare the risk of acute kidney injury (AKI) between hospitalized children who received intravenous contrast media for imaging examinations and those who did not. Methods This retrospective cohort study enrolled patients aged 0-18 years with serum creatinine levels before and after imaging examinations from 2015 to 2020 at Beijing Children's Hospital. Participants were classified into an exposure group or a control group. Log-binomial regression analysis was used to estimate the adjusted risk ratio (aRR) value for the association between exposure to contrast media and consequential AKI. After which, inverse probability treatment weighting was used to reduce systematic differences in baseline characteristics among the groups. Moreover, subgroup and sensitivity analyses were performed. Finally, multivariate logistic regression analysis was performed to identify risk factors for pediatric AKI. Results In total, 3061 pediatric patients were included in the analyses (median age, 4.5 [IQR, 1.3-8.9] years, 1760 males). According the KDIGO definition of AKI, the incidence of AKI in the exposure group, and the control group were 7.4% and 6.5%, respectively; furthermore, the aRR was 1.35 (95% CI: 1.31-1.39). In patients underwent CT, the risk of AKI in the exposure group of contrast media increased compared with the control group and the aRR was 1.39 (95% CI: 1.09-1.78). However, it is not observed in patients underwent MRI (aRR: 1.36; 95% CI: 0.96-1.95). According to our subgroup analysis of pediatric patients aged ≥ 2 years (aRR: 1.38; 95% CI: 1.05-1.82) and sensitivity analysis (aRR: 1.32, 95% CI: 1.08-1.61), the risk of AKI in the exposure group was greater than that in the control group. An increased risk to exposure to contrast media was seen in females (aRR: 1.41, 95% CI: 1.05-1.89) rather than males (aRR: 1.30, 95% CI: 0.99-1.70). According to the multivariate logistic regression analyses, the baseline eGFR (OR: 1.02; 95% CI: 1.01-1.03) and comorbidities (OR: 2.97; 95% CI: 1.89-4.65) were risk factors, while age (OR: 0.87; 95% CI: 0.84-0.91) was a protective factor against AKI. Conclusion The evidence from the present study suggested that the increased risk of AKI in hospitalized children induced by intravascular contrast should not be ignored.